Unveiling the role of circulating periostin in patients with idiopathic pulmonary fibrosis: A prognostic meta-analysis - Alghwyeen, Wasfi; Mohamed, Shrouk F.; Hashim, Ahmed Shamil; Tawfik, Abdelrahman M.; Kertam, Ahmed (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Periostin measurement has been suggested as a noninvasive biomarker for assessing the likelihood of IPF progression and predicting patient outcomes, but these results aren't entirely consistent. Therefore, we conducted a meta-analysis to study the relation between serum periostin and IPF.Methods: We conducted a comprehensive search in major electronic biomedical databases of (PubMed, Scopus, Cochrane Library, EMBASE and Web of Science) spanning from inception to September 2024.  Meta-analysis of included studies was done, and quantitative data were pooled as standardized mean difference (SMD), odd rations (ORs) and coefficient (r) values , with corresponding 95% confidence intervals (CIs).Results: Eleven articles were included in final meta-analysis. Our results showed that there was no significant difference in periostin levels between IPF patients and healthy controls (SMD: 2.59, 95% CI: -0.59 to 5.77, p= 0.11). Moreover, it was shown that IPF patients with a progressive disease have higher periostin levels compared to those who remain stable (SMD: 0.52, 95% CI: 0.29 to 0.75, p